ClimBeR Policy Influence in Morocco, Philippines and Zambia - Ogada, Maurice Juma (CGIAR System Organization, 2024)
This report assesses the policy influence of the CGIAR Initiative on Climate Resilience (ClimBeR) in Morocco, the Philippines, and Zambia. Through a combination of evidence-based research, strategic partnerships, and targeted interventions, ClimBeR contributed to the shaping of climate adaptation and resilience strategies in these countries. The initiative focused on addressing key climate challenges, including drought, flooding, and rising temperatures, by integrating innovative approaches and fostering collaboration among stakeholders. The findings underscore ClimBeR's impact in strengthening institutional frameworks and shaping climate-resilient agricultural systems. Despite its achievements, the report highlights the need for sustained investment and extended timelines to ensure the long-term sustainability and scalability of its contributions.